Online Characterization of Single Airborne Carbon Nanotube Particles Using Optical Trapping Raman Spectroscopy. Issue 8 (August 2019) - Gong, Zhiyong; Pan, Yong-Le; Videen, Gorden; Wang, Chuji
Carbon nanotubes (CNTs) have become recognized as a potential environmental and health hazard as their applications are broadening and manufacturing costs are reducing. Fundamental information of CNTs in air is of significant importance to our understanding of their environmental fate as well as to further applications. Extensive efforts have been made over decades on characterizing CNTs; however, a majority of the studies are of bulk or CNTs dispersed on substrates. In the present study, we characterize single CNT particles in air using optical trapping Raman spectroscopy (OT-RS). Different types of CNT particles, as well as glassy carbon spheres, were optically trapped in air. Their physical properties were viewed by microscopic bright field images and scattering images; their chemical properties and structural information can be inferred from characteristic Raman bands. The system can also spatially resolve the morphology and chemical distribution of optically trapped CNT particles in air. The OT-RS technique combines single-particle morphological and chemical information and offers an online method to characterize the physicochemical properties of single CNT particles at their native states in air.